CULTURAL AND CONTEXTUAL PROBLEMS IN THE TRANSLATION OF SPECIALIZED TERMINOLOGY - G‘afurova Nazokat Bakhriddin’s daughter (Ustozlar uchun, 2025)
Annotation: This article explores the cultural and contextual challenges that arise in the translation of specialized terminology. It examines theoretical frameworks including pragmatic translation, the concept of realia, untranslatability, and cultural equivalence. Drawing on examples from medical, legal, and technological fields, the paper discusses how linguistic and extra-linguistic factors affect term transfer. The analysis suggests that successful translation requires balancing terminological accuracy with cultural intelligibility.